1996
DOI: 10.2307/1592277
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Method of Aerosol Challenge for Testing the Efficacy of Mycoplasma gallisepticum Vaccines

Abstract: A special chamber was constructed with the goal of controlling the process of aerosol infection of chickens with Mycoplasma gallisepticum (MG). The virulent Australian MG field strain Ap3AS was used in each of three experiments. The response to infection of layer-strain pullets was measured serologically, by the incidence and severity of gross lesions in tracheas and air sacs, and by the relative numbers of MG isolated from tracheas and air sacs 2 wk after challenge. In two of the experiments tracheal sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Chickens were challenged by aerosol with M. gallisepticum for 10 min in an isolation chamber as described previously (Whithear et al, 1996). As previous studies have shown that exposure to media alone has no effect upon the respiratory tract (Whithear et al, 1996), control birds were left unchallenged.…”
Section: Methodsmentioning
confidence: 99%
“…Chickens were challenged by aerosol with M. gallisepticum for 10 min in an isolation chamber as described previously (Whithear et al, 1996). As previous studies have shown that exposure to media alone has no effect upon the respiratory tract (Whithear et al, 1996), control birds were left unchallenged.…”
Section: Methodsmentioning
confidence: 99%
“…Routes of infection include aerosol, eye drop, intranasal, intratracheal, direct air sac injection, and spray application (Rodriguez & Kleven, 1980;Lin & Kleven, 1982;Levisohn et al, 1983;Levisohn & Dykstra, 1987;Nunoya et al, 1987;Naylor et al, 1992;Whithear et al, 1996;Ganapathy & Bradbury, 1998;Kollias et al, 2004;Feberwee et al, 2005). Co-infectious agents, including Newcastle disease virus (NDV), infectious bronchitis virus (IBV), and Escherichia coli, have also been used to study their effects on or the enhancement of the disease process (Rodriguez & Kleven, 1980;Bradbury, 1984;Nakamura et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The droplet size delivered by this apparatus has been determined previously as between 1 and 10 μm, with the majority of particles <5 μm at an air flow of 15 l/min (Whithear et al, 1996). Aerosols of M. gallisepticum delivered to chickens using this method have induced lesions consistently in the air sacs and the trachea, indicating that there is infection of the upper and lower respiratory tract (Whithear et al, 1990(Whithear et al, , 1996Gaunson et al, 2000Gaunson et al, , 2006. The strain comparison study described here was carried out in order to identify the more appropriate strain for the infection model.…”
Section: Discussionmentioning
confidence: 99%
“…The following day, all of the birds were wing-tagged for identification and weighed. At day 0, the turkeys in the negative control group were exposed to MB using a nebulizer to deliver an aerosol into a cylindrical infection chamber (Whithear et al, 1996). Turkeys in the second group were exposed to an aerosol of a culture containing 7.06 × 10 8 colour-changing units (CCU)/ml M. gallisepticum Ap3AS and those in the third group to an aerosol of a culture containing 1.0 × 10 8 CCU/ml M. gallisepticum 100809/31.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation